## Help me!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!

Question

Help me!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!

in progress 0
4 years 2020-11-13T21:49:59+00:00 2 Answers 64 views 0

## Answers ( )

1. Đáp án:

1/ $A=(6a+2)^2$

2/ $B=(6a-2b-1)^2$

Giải thích các bước giải:

1/ $A=(5a+5)^2+10(a-3)(1+a)+a^2-6a+9$

$=[5(a+1)]^2+2.5(a-3)(a+1)+(a-3)^2$

$=[5(a+1)+(a-3)]^2$

$=(5a+5+a-3)^2$

$=(6a+2)^2$

2/ $B=(6a-2)^2+4(3a-1)(1-2b)+(2b-1)^2$

$=[2(3a-1)]^2+2.2(3a-1)(1-2b)+(1-2b)^2$

$=[2(3a-1)+(1-2b)]^2$

$=(6a-2+1-2b)^2$

$=(6a-2b-1)^2$

2. Đáp án:

$$A = {\left( {6a + 2} \right)^2}$$

Giải thích các bước giải:

$$\begin{array}{l} A = {\left( {5\left( {a + 1} \right)} \right)^2} + 2.5\left( {a + 1} \right)\left( {a – 3} \right) + {\left( {a – 3} \right)^2}\\ = {\left( {5a + 5 + a – 3} \right)^2}\\ = {\left( {6a + 2} \right)^2}\\ B = {\left( {2\left( {3a – 1} \right)} \right)^2} + 2.2\left( {3a – 1} \right).\left( {1 – 2b} \right) + {\left( {2b – 1} \right)^2}\\ = {\left( {2\left( {3a – 1} \right)} \right)^2} + 2.2\left( {3a – 1} \right).\left( {1 – 2b} \right) + {\left( {1 – 2b} \right)^2}\\ = {\left( {6a – 2 + 1 – 2b} \right)^2}\\ = {\left( {6a – 2b – 1} \right)^2} \end{array}$$